In Searching of Sources of Family Business Succession Failure - Magdalena BARYŃ; Oliwia ŚLUSARCZYK (Communications of International Proceedings, 2020)
One of the basic goals of family businesses, determining the essence and uniqueness of these entities, is to last for generations. That is why successful succession is one of the most important tasks facing family businesses. Meanwhile statistics show that few companies pass into the hands of the next generations. The aim of this article is to examine the succession situation in Polish family businesses and to try to answer the question what factors may determine the failure of an intergenerational transfer. The research is based on two main secondary sources which are reports from studies conducted among Polish owners of family businesses and potential successors. Research results show that Polish family entrepreneurs make many mistakes that hinder the successful implementation of the succession process. These errors include, among others, insufficient knowledge of the time horizon of succession, lack of proper communication regarding succession, or lack of formal, written confirmation of succession. A very important factor affecting the low effectiveness of succession processes is the low interest of successors in taking over the family business. It may result from internal factors, relationships in family as well as factors from the social environment. To increase the chances of successful succession of Polish family businesses, it is therefore necessary to act in many ways. First, the owners' knowledge should be raised so that they can plan and then carry out the succession process. Secondly, it is necessary to convince potential successors that taking over the family business is a challenge that they can cope with and which will give them professional satisfaction. Thirdly, it is necessary to ensure the society that family businesses are a treasure of the national economy, and successors take over companies with a sense of well-understood duty and are able to contribute a lot to them.
Keywords: Failure in Succession; Family Business; Family Firms; Succession; Transgenerational Transfer.